Tendon structure, clinical tests, and pain during-loading in young female competitive gymnasts - Steinberg, N.; Elbaz, L.; Eliakim, A.; Nemet, D.; Bar-Sella, S.; Peleg, S.; Dar, G. (Journal of Sports Sciences, 2024)
To examine the relationship between Achilles-tendon (AT) and patellar-tendon (PT) structure, clinical-examination and tendon pain in young gymnasts; and, to explore the associations between these factors and age, maturation, and training-load. Two hundred and seventy-four female gymnasts (aged 12.1±1.9 yrs) were assessed for anthropometric measures, pubertal-stage, and training-load. They had clinical-tests (pain-on-palpation for AT and pain-on-palpation and Royal-London Hospital-Test for PT), were asked about tendon-pain during-loading and were assessed for tendon-structure. Gymnasts with positive clinical-tests (with and without pain during-loading) presented a significantly higher prevalence of disorganized AT and PT compared to gymnasts with negative clinical-tests (with and without pain during-loading) (p<0.05). A significant pubertyXpositive clinical-test interaction was found for disorganized PT structure, whereby a disorganized structure was more prevalent among post-pubertal gymnasts with positive clinical-tests compared to pre-pubertal participants with negative clinical-tests (F(1, 263)=9.436, p=0.002). In gymnasts with positive clinical-tests, significant correlations were found between disorganized AT and PT structures and age, and training-load (p<0.05). An increased prevalence of disorganized tendon structure (regardless of pain during-loading) was seen in participants with positive clinical-tests. This disorganized tendon-structure was found to be significantly related to increased age, post-pubertal stage, and higher training hours in gymnasts with positive clinical-tests.